G6PD Enzyme Activity in Newborns and Children: Reference Values by the Quantitative Colorimetric Method and a Comparison with the Fluorescent Spot Test - Manowong, Suphara; Tachawong, Narumon; Waiyo , Sugunya; Charoenkwan, Pimlak (Biomedical Sciences and Clinical Medicine, 2022)
OBJECTIVE This study aimed to establish G6PD enzyme activity reference levels in newborns and children by the quantitative colorimetric method and to compare the results with the fluorescent spot test. METHODS Leftover blood samples from newborns and children that were sent for G6PD measurement and tested by the fluorescent spot test at the Pediatric Laboratory, Faculty of Medicine, Chiang Mai University were further tested by the quantitative colorimetric method. The values were analyzed according to age group and the two methods were compared. RESULTS There were 111 newborns (76 males, mean age 3.9±3.5 days) and 182 children (81 males, mean age 7.4±4.2 years). The mean G6PD enzyme activity levels in normal male and female newborns using the colorimetric method were 12.7±2.9 and 13.2±2.0 IU/g Hb, and in normal male and female children were 10.7±4.0 and 11.3±3.2 IU/g Hb, respectively. By the fluorescent spot test, 33 (11.3%), 7 (2.4%) and 253 (86.3%) samples were classified as G6PD deficient, intermediate-deficient and normal G6PD status, respectively. The sensitivity and specificity by the fluorescent spot test of males were 93.3, 98.4% and of female were 45.0, 99.1%, respectively. CONCLUSIONS G6PD enzyme activity reference levels in newborns and children by a colorimetric method were established. The fluorescent spot test shows a good performance in males, but a lower performance in intermediate-deficient females. Therefore, females should be tested by the colorimetric method.